2017
DOI: 10.2196/resprot.8260
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Mental Health Care Program and Home-Based Training for Mothers of Children With Autism Spectrum Disorder in an Urban Population in Bangladesh: Protocol for a Feasibility Assessment Study

Abstract: BackgroundMothers of children with autism spectrum disorder (ASD) have reported a higher level of depression than mothers of children with other neurodevelopmental disorders in both developed and developing countries. Mothers are the lifetime caregivers of children with ASD, and a high burden of depression can negatively impact their ability to provide care. However, access to mental health services in primary care is limited, given the scarcity of qualified providers in Bangladesh.ObjectiveWe aim to pilot the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The national survey of ASD in Bangladesh conducted in 2013 reported the prevalence of ASD to be 15.5 per 10,000 children, with a higher prevalence of ASD in urban (300 per 10,000 children) than rural areas (6.8 per 10,000 children) [NCDC, RCHCIB, BMRC, 2013]. Recently, one study conducted in a rural subdistrict in Bangladesh reported that the prevalence of ASD was 7.5 per 10,000 children, indicating the prevalence of ASD may be increasing in Bangladesh than previously reported [Akhter et al, 2018].…”
Section: Burden Of Asd In Bangladeshmentioning
confidence: 99%
See 2 more Smart Citations
“…The national survey of ASD in Bangladesh conducted in 2013 reported the prevalence of ASD to be 15.5 per 10,000 children, with a higher prevalence of ASD in urban (300 per 10,000 children) than rural areas (6.8 per 10,000 children) [NCDC, RCHCIB, BMRC, 2013]. Recently, one study conducted in a rural subdistrict in Bangladesh reported that the prevalence of ASD was 7.5 per 10,000 children, indicating the prevalence of ASD may be increasing in Bangladesh than previously reported [Akhter et al, 2018].…”
Section: Burden Of Asd In Bangladeshmentioning
confidence: 99%
“…The awareness of ASD is not widespread and the contemporary conceptions of ASD as practiced among few providers in urban areas are severely restricted. The prevalence of recognized and treated ASD is therefore likely to remain low with poor levels of awareness, diagnosis, and services [NCDC, RCHCIB, BMRC, 2013].…”
Section: New Evidence Of Asd In Relevance To Lmic and Contextualizatimentioning
confidence: 99%
See 1 more Smart Citation
“…Though several works 45 , 46 in this relevant area to determine the mental health of the children with ASD in Bangladesh, in this study, we specifically identify the behavioral changes of the children with ASD in Bangladesh during the COVID-19 lockdown period. Compared to other studies, in this work, we have deployed our developed mCARE: APP and mCARE: SMS tools among our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…For the neurodevelopmental group overall, the global burden of depression is highest among mothers of children with autism spectrum disorders (ASD) (Weitlauf et al, 2014). A recent study from Bangladesh demonstrated that about 50% of mothers of children with ASD experienced major depressive disorder (MDD), and half of the mothers with MDD presented with a concurrent major depressive episode (MDE) (Naheed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%